Impact of 25(OH)D3 on spontaneous reperfusion and SYNTAX score in patients with ST-elevation myocardial infarction - Oğuz Akkuş; Mustafa Topuz; Fahrettin Öz; Hazar Harbalıoğlu; Hasan Koca; Mehmet Kaplan; Ömer Şen; Atilla Bulut; Mustafa Gür (KARE Publishing, 2018)
Objective: The aim of this study was to evaluate the potential relationship between 25-hydroxyvitamin D3 (25[OH]D3), the Synergy between PCI with Taxus and Cardiac Surgery (SYNTAX) score, and spontaneous reperfusion (SR) in patients with ST-elevation myocardial infarction (STEMI). Methods: A total of 148 consecutive patients with acute STEMI who underwent primary percutaneous coronary intervention were retrospectively enrolled in the study. Results: In all, 36 patients with a TIMI 3 flow score (spontaneous reperfusion [SR]) before coronary intervention constituted Group 1, and 112 patients with a TIMI flow score of 0-2 served as Group 2. The SYNTAX score and the in-hospital major adverse cardiovascular event (MACE) rate were significantly higher in Group 2 (p<0.001, p=0.012, respectively). The mean 25(OH)D3 level was significantly higher in Group 1 (p=0.003). Age, Killip class, left ventricular ejection fraction, and N-terminal pro-B-type natriuretic peptide were correlated with the SYNTAX score, and 25(OH)D3, troponin-I, C-reactive protein, and creatinine were weakly correlated with the SYNTAX score. Multilogistic regression analysis indicated that the SYNTAX score (p<0.001), Rentrop collateral (p=0.049), and troponin-I (p=0.004) were significantly effective at predicting SR, and 25(OH)D3 (p=0.079) and high-density lipoprotein (p=0.055) were borderline effective. Conclusion: A lower level of 25(OH)D3 may be associated with the absence of SR, increased disease severity, and in-hospital MACE rates in patients with STEMI.